Cluster ion beam generation from a wetted needle emitter for organic secondary ion mass spectrometry (organic SIMS) using a protic ionic liquid, propylammonium nitrate. (23rd September 2018) - Fujiwara, Yukio; Saito, Naoaki
Abstract : Rationale: Propylammonium nitrate (PAN, [C3 H7 NH3 ][NO3 ]), a protic ionic liquid, has an active proton in its molecular structure, so that it can promote protonation. In addition, PAN has high aggregability, so that it tends to form large aggregated (or cluster) ions. These features will be desirable for cluster ion beams in secondary ion mass spectrometry (SIMS) of organic materials. The aggregability may enable us to generate a cluster ion beam from a needle tip wetted with PAN by electrospray in vacuum. For these reasons, cluster ion beam generation was investigated using an externally wetted needle emitter. Methods: A sharpened glass rod was used as a needle emitter. PAN was electrosprayed in vacuum using the needle emitter to generate a cluster ion beam. Beam characteristics were investigated with an apparatus for measuring transient responses of a beam current. SIMS experiments were also performed using the cluster ion beam as a primary ion beam; arginine and polyethylene glycol (PEG300) were analyzed. Results: A stable cluster ion beam was generated from the needle emitter wetted with PAN. The ion beam consisted of mixed cluster ions whose m/z ranged from about 180 to 5000 or higher. The cluster ion beam successfully produced protonated molecules [M + H] + (M denotes arginine and PEG molecules) with relatively little fragmentation. Adduct ions [M + C3 H7 NH3 ] + formed by propylammonium‐attachment reaction were also detected for PEG. Conclusions: It has been demonstrated that a needle emitter wetted with PAN can generate a cluster ion beam that includes massive cluster ions. The cluster ion beam proved to be helpful in producing molecular secondary ions and suitable for a primary ion beam in organic SIMS.